First snow ski tracks : prolonging of the natural season of the cross-country skiers in Finland - Repo, Katja (2018)
Cross-country skiing is one of the national sports in Finland. It is a widely practiced sport and leisure activity that has a long history. Traditionally cross-country skiing has been practiced outdoors for free on natural tracks during winter months. One of the largest challenges to cross-country skiing is global warming. It causes challenges to winter sports such as cross-country skiing because winters are getting warmer. This means that the snow cover is thinner and cross-country skiing season shorter.